John Lydgate's dance of death and related works - Cook, Megan L. (Megan Leigh), 1981-; Strakhov, Elizaveta, 1984-; Lydgate, John, 1370?-1451? (Middle English texts (Kalamazoo, Mich.), 2019)
"This volume brings together new editions of both texts of John Lydgate's fifteenth-century poem, The Dance of Death, with related Middle English verse from the fourteenth and fifteenth centuries. It also includes a new translation of Lydgate's French source, the Danse macabre. Together, these poems showcase the power and versatility of the danse macabre motif, offering a vivid window into life and death in late medieval Europe. In these poems, we see Death itself help readers remember and process the fundamental paradox of death's universality yet irremediable specificity. In vivid, often grotesque, and darkly humorous terms, these poems ponder life's fundamental paradox: while we know that we all must die, we cannot imagine our own death"--